Um dilema feminino: o câncer de colo do útero - AMORIM, Linamar Teixeira de (2009)
The treatment of uterine cancer, a slow-growing form of the disease, is particularly effective in regard to precursor lesions. In order to understand this illness from the perspective of health sociology, this study focused on women afflicted with uterine cancer. Semi-structured interviews were employed in an attempt to perceive these women s representations. The interviews revealed the coexistence of positive and negative aspects in experiences with cancer and confirmed the stigma borne by both the illness and the treatment. Results showed that public health policies and available health services need to complement individual prevention measures in attributing priority to information about the illness and the treatment, thus covering all dimensions of people s lives. This conclusion highlights the need for a humanized health system that guarantees access to quality health services and exposes the interface between sociology and health, which is essential for the promotion of humanization within the sociocultural context of the health-illness process.